1968
DOI: 10.1177/004051756803800710
|View full text |Cite
|
Sign up to set email alerts
|

Felting Shrinkage of Plain-Knitted Wool Fabrics

Abstract: The dependence of felting shrinkage rate upon yarn count, cover factor, shrink proofing level, and severity of washing action has been examined, using plain-knitted wool fabrics. The investigation was a factorial arrangement with 54 combinations of factors for each of two shrink-proofing treatments. The results were subjected to analyses of variance. The felting shrinkage rate was lowered by increasing the cover factor, by increasing the level of shrinkproofing treatment, and by decreasing the severity of wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Felting shrinkage is dependent upon a large num= ber of factors, the most critical associated with the fabric structure being the &dquo;cover factor.&dquo; Some recent results [1] reveal the dependence of felting shrinkage rates upon cover factor for plain-knit fabrics; similar results have been reported by other authors. From these and other unpublished data, it can be shown that this relationship is described satisfactorily by the equation where R is area shrinkage rate, c is cover factor, and A and B are constants.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Felting shrinkage is dependent upon a large num= ber of factors, the most critical associated with the fabric structure being the &dquo;cover factor.&dquo; Some recent results [1] reveal the dependence of felting shrinkage rates upon cover factor for plain-knit fabrics; similar results have been reported by other authors. From these and other unpublished data, it can be shown that this relationship is described satisfactorily by the equation where R is area shrinkage rate, c is cover factor, and A and B are constants.…”
supporting
confidence: 77%
“…Two washes were done in an agitator machine having a stationary drum and a central vertical agitator, oscillating at 60 c/min. Other details of this test have been described previously [1]. The third was carried out in a &dquo;Cubex&dquo; machine, the details of which have also been described [2], but the liquor level was altered to 10 liters, greatly increasing the severity of the wash action.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the wash conditions have been given , previously [2]. , The reference dimensions from which length and width changes of the samples were calculated were those of the wet-relaxed state.…”
Section: Contribution Of Single-fiber Setmentioning
confidence: 99%
“…Single fibers may affect and control filtration performance through their geometric properties, surface finish, electrical properties, hardness, and other mechanical properties. The mechanism of capture of a particle by a single fiber has received the attention of many workers, who have examined the role of diameter [2][3][4], shape ES, 6J, surface [7,8], modulus [9], and hardness [9], as well as the ambient relative humidity (10) and the electrical charge on the fiber [11]. When a gas stream is passed through a filter medium, there are three basic mechanisms of particle capture: direct interception,…”
Section: Introductionmentioning
confidence: 99%